1989
DOI: 10.1103/physrevlett.62.1017
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between projectilelike and targetlike fragments in the reaction+2744-MeV/nucleon

Abstract: Correlations between projectilelike and targetlike fragments have been measured in the reaction 27 Al + 44-MeV/nucleon 40 Ar. These correlations can be consistently interpreted in the framework of an abrasion model including dissipation. However, they can also be described by a binary process in which, before decaying sequentially by particle emission, projectile and target share an approximately equal amount of excitation energy with no significant mass transfer.PACS numbers: 25.70.Np For projectiles of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

1990
1990
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…6 where the A/Z ratio of the primary fragments, which was assumed to be equal to the A/Z ratio of the projectile, is indicated by the dashed line. As shown in [8], this correlation is well reproduced by a fast abrasion model. For masses ./I~F below 30, the agreement between the calculation and the data is excellent.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…6 where the A/Z ratio of the primary fragments, which was assumed to be equal to the A/Z ratio of the projectile, is indicated by the dashed line. As shown in [8], this correlation is well reproduced by a fast abrasion model. For masses ./I~F below 30, the agreement between the calculation and the data is excellent.…”
Section: Resultssupporting
confidence: 59%
“…Some indication has been obtained through various experiments, that may give indirect estimates [4][5][6][7][8]. Some indication has been obtained through various experiments, that may give indirect estimates [4][5][6][7][8].…”
Section: I) Excitation Energiesmentioning
confidence: 99%
“…For the same reaction, it has been shown previously [3] that PLF-TLF coincidence data could be interpreted as the result of a two-step process: a binary collision between the projectile and the target with a very small net exchange of nucleons leading to primary excited projectile and target nuclei which then decay by particle emission. Within this hypothesis, it was shown that the projectile and target primary fragments share an amount of excitation energy which evolves from equal sharing for peripheral collisions to sharing in the mass ratio (equal temperature) for more central collisions.…”
Section: The Binary Reaction Hypothesismentioning
confidence: 99%
“…They de-excite by emission of light particles and/or fragments with velocity close to those of the projectile and of the target respectively. Later, a coincidence experiment [3] between projectile-like and target-like (TLF) fragments using the same reaction ( 40 Ar+ 27 Al reaction at 44 A.MeV) showed a strong correlation between PLFs in the forward direction and TLFs detected in a wide angular range up to 90 • . Both a three-body abrasion-ablation mechanism (low excitation energy in the primary PLFs and TLFs) or a simple two-body mechanism like the so-called "deep inelastic" collisions (high excitation energy in the primary projectile and target nuclei) were able to account rather well for the experimental results.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, this is true for the reverse kinematics reaction Ar + Al, investigated by several authors [8][9][10][11][12][13][14][15][16][17][18]. In this paper, we aim to study light charged particle (LCP) emission from the PLF, in E/A = 44 and 77 MeV 40 Ar + 27 Al collisions.…”
Section: Introductionmentioning
confidence: 99%